Implementasi Nilai-Nilai Pendidikan Multikultural Kabupaten Subang - Adam Hasyim; Aldo Muhammad Derlan (Institut Agama Islam Negeri Bengkulu, 2023)
Abstract: Implementation Of Multicultural Educational Values In SubangÂ DistrictThis study discusses the implementation of multicultural education in Subang district. The fact shows that Subang Regency currently accommodates adequate plurality and multiculturalism, besides that Subang is also an area that takes advantage of the current changing times, with the target being industrial areas and metropolitan smart cities on the Rebana triangle and also the presence of the Patimban International Port, this is the case Of course, it has a lot of good potential if it can be maximally empowered, but it is prone to conflicts and frictions that can cause divisions if it is not managed properly. Through a qualitative descriptive research method, it describes how the conditions of multicultural reality in Subang Regency and its implementation analyze the values of multicultural education in the midst of the times that have an impact on people's lives. This management can be done by implementing the values of multicultural education in an area, especially in Subang, education has an important role in guiding the social order to have attitudes and views of mutual respect, tolerance, democracy, justice and mutual understanding.Abstract: Implementasi Nilai-Nilai Pendidikan Multikultural Di Kabupaten SubangPenelitian ini membahas tentang implementasi pendidikan multikultural di kabupaten subang. Kenyataan menerangkan bahwa kabupaten subang saat ini mengakomodasi plularitas dan multikultural yang memadai, di samping itu subang juga merupakan daerah yang terdampak perubahan zaman saat ini, dengan ditargetnya menjadi wilayah industri dan kota smart metropolitan diÂ segi tiga rebana dan juga hadirnya Pelabuhan internasional patimban, hal demikian tentu memiliki banyak potensi yang baik apabila dapat diberdayakan dengan maksimal, akan tetapi rawan konflik serta gesekan-gesekan yang menimbulkan perpecahan apabila tidak dibina dengan baik. Melalui metode penelitian deskriptif kualitatif, memaparkan bagaimana kondisi realitas multikultural di kabupaten subang dan menganalisis implementasi nilai-nilai pendidikan multikultural di tengah perkembangan zaman yang berdampak pada kehidupan masyarakatnya. Pengelolaan tersebut bisa dilakukan dengan upaya implementasi nilai-nilai Pendidikan multikultural dalam suatu daerah khususnya di Subang, pendidikan memiliki peranan penting dalam membimbing tatanan masyarakat untuk memiliki sikap dan pandangan saling menghargai, toleransi, demokratis, adil dan saling memahami